Beckman Data Sheet Describes Phosphoramidite Chemicals - Schneider, Ilene (1985)
The press release discusses Beckman documentation of phosphoramidites availabe for use with DNA synthesizers.
Keywords: Marketing; DNA--Synthesis; Beckman Instruments, Inc.